1954
DOI: 10.4153/cjm-1954-054-3
|View full text |Cite
|
Sign up to set email alerts
|

Note on the Algebra of S-Functions

Abstract: Considerable advance has been made recently towards a systematic method of evaluating the “product” {μ} ꕕ {λ}, most notably in the methods of Robinson (3), Littlewood (2), and Todd (5) and the differential operator technique of H. O. Foulkes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1956
1956
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…They are helpful, as a metaphor [22], for developing self-esteem and self-efficacy [23][24][25], confidence [26], positive behavior [27], and are also effective in fostering trust and attachment [21]. Therefore, horses have been used in a variety of therapeutic service contexts, such as learning and counselling programs in correctional facilities [28], mental health facilities [26], and social services [29], as well as with high-risk youths and veterans who have experienced emotional and behavioral trauma [30,31].…”
Section: The Usefulness Of Eal For Individuals With Igdmentioning
confidence: 99%
See 1 more Smart Citation
“…They are helpful, as a metaphor [22], for developing self-esteem and self-efficacy [23][24][25], confidence [26], positive behavior [27], and are also effective in fostering trust and attachment [21]. Therefore, horses have been used in a variety of therapeutic service contexts, such as learning and counselling programs in correctional facilities [28], mental health facilities [26], and social services [29], as well as with high-risk youths and veterans who have experienced emotional and behavioral trauma [30,31].…”
Section: The Usefulness Of Eal For Individuals With Igdmentioning
confidence: 99%
“…Therefore, EAL offers practical learning through mounted and unmounted activities to improve participants' social functioning, self-awareness, understanding, empathy, accomplishment, confidence through problem-solving, and interpersonal skills [32]. According to previous studies, EAL was effective in improving attachment, confidence, communication, empathy, and social skills in adolescents [30], encouraging hope and decreasing depression in at-risk youths [19], and decreasing trauma symptoms [31,33,34], as well as growing self-control, greater family intimacy, and lesser impulsivity in adolescents with attention-deficit hyperactivity disorder (ADHD) [30].…”
Section: The Usefulness Of Eal For Individuals With Igdmentioning
confidence: 99%
“…In recognition of all the above, animal-assisted interventions (AAIs) are being frequently used as complementary interventions for trauma survivors in general [43][44][45], specifically among veterans [26,33,[46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64]. AAIs might benefit trauma survivors by facilitating enhanced engagement with conventional interventions and/or, after rigorous studies demonstrating benefit, serve as stand-alone evidence-based treatments.…”
Section: Conventional Interventions For Trauma Exposurementioning
confidence: 99%
“…There is now emerging literature reporting investigations of EAS interventions for veterans with trauma histories. This review identified 23 studies [26,33,[46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][108][109][110][111] in the literature (Table 1). However, of these, only three [47,52,53] had a control group and only one [52] was a randomized trial.…”
Section: Overview Of the Extant Literaturementioning
confidence: 99%
“…The following table presents a (non-exhaustive) list of some of the known results in this direction. ]] in terms of Schur functions [18] Since general formulae for the coefficients a ν λ,µ have been elusive, various methods for computing plethysm have been developed [5,6,9,13,14,23,26,35,43,45,46] as well as representation-theoretic approaches [4,11,20,32,33,37].…”
Section: Introductionmentioning
confidence: 99%